ANCIENT EARTHQUAKE DISLOCATIONS IN THE AREA OF ELBRUS VOLCANO, NORTH CAUCASUS - Rogozhin E.A.; Gurbanov A.G.; Marakhanov A.V.; Ovsyuchenko A.N.; Spiridonov A.V.; Burkanov E.E. (My University, 2004)
New data have been obtained for the ancient, previously unknown large earthquakes that occurred during the Holocene in the central Caucasus region in the vicinity of Elbrus Volcano. The radiocarbon datings of the paleoseismic dislocations and the dating of the products of the old eruptions of the volcano suggest that at least four large eruptions of the volcano and four earthquakes with magnitudes of 6.5-7.0 had occurred during the last 7 thousand years. Although no synchronism has been found between the volcanic and seismic events, some earthquakes might have been associated with particular large eruptions.
Keywords: EARTHQUAKE DISLOCATIONS; ELBRUS VOLCANO; LARGE EARTHQUAKES; HOLOCENE; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен